Hubungan Kompetensi Sosial Guru dengan Hasil Belajar IPS Kelas IV Sekolah Dasar - Sitti. Jauhar; Asriadi Asriadi; Fadliyah Mubakhirah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2023)
This research is a quantitative research with the type of correlational research which aims to determine the significant relationship between the teacher's social competence and the social studies learning outcomes of class IV. Based on the results of the study, it showed that the social competence of teachers was included in the very good category. Then based on the results of inferential statistics, the value of t_count is 0,54 greater (<) the value of t (table) 0,2706 at a significance level of 5%, thus H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between teacher social competence and social studies learning outcomes in grade IV SD Inpres 12/79 Lonrae, Tanete Riattang Timur District, Bone Regency.